The Conception of the Universal Dual Categories of Wisdom in Movses Khorenatsi' s Doctrine of History - Kocharyan, Romik (Տիգրան Մեծ)
The author of this article presents a system of 12 dual categories of the philosophy of history first outlined in his monograph dedicated to the study of the philosophical-methodological aspects of Movses Khorenatsi‟s great work “The History of Armenians”. The system of 12 dual categories of the wisdom of history suggested by the author of this article demonstrates that Movses Khorenatsi‟s theory of history builds a firm conception of philosophizing “science of history”.
Keywords: History of philosophy